Father Involvement as a Psychological Resource: A Literature Review on Building Resilience and Career Confidence in Emerging Adults - Febrina Meirel Taroreh; Endang Widyorini (Universitas Muhammadiyah Metro, 2026)
This literature review explores the role of father involvement as a psychological resource in shaping the resilience and career confidence of emerging adults. As social and economic changes demand greater adaptability, understanding the father’s contribution to emotional and developmental outcomes becomes increasingly essential. Using a narrative literature review method, this study analyzed 25 empirical and theoretical articles published between 2014 and 2025, selected through keyword searches and snowballing techniques in Google Scholar and Scopus. The findings are organized into three main clusters: (1) father involvement as a psychological resource that enhances emotional regulation, self-confidence, and motivation; (2) resilience as a developmental outcome reflecting the influence of paternal warmth, autonomy support, and consistent engagement; and (3) career confidence as a capability strengthened by fathers’ encouragement and guidance in decision-making and self-belief. Across studies, father involvement emerges as a key determinant of adaptive functioning and emotional well-being, serving as a foundation for self-reliance and personal growth. The review concludes that fathers’ emotional presence and active participation play a transformative role in preparing young adults to navigate life challenges and career transitions. Father involvement, therefore, represents not only a familial relationship but also a form of psychological capital essential for developing resilient and capable future generations.Â